1996
DOI: 10.1007/s002689900067
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Organ Failure following Severe Trauma

Abstract: Multiple organ failure (MOF) is considered to be the leading cause of death after severe trauma. Although there is extensive literature on MOF, little is known about the pattern, sequence, and onset of this clinical syndrome. The first goal of this clinical study was to define MOF; the second was to assess the typical onset, sequence, and pattern of MOF; and the third was to define certain risk factors for the development of MOF in 342 multiple trauma patients. Patients with an Injury Severity Score (ISS): > 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
103
2
13

Year Published

2001
2001
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(122 citation statements)
references
References 22 publications
3
103
2
13
Order By: Relevance
“…In spite of this, our findings are in agreement with previous research that SOFA scores have good discrimination between survivors and nonsurvivors [32]. In addition, as in prior research [33][34][35][36], multiple organ dysfunction evidenced by high SOFA scores are associated with higher mortality. The use of proxy variables for SOFA scores has been validated in prior research.…”
Section: Discussionsupporting
confidence: 76%
“…In spite of this, our findings are in agreement with previous research that SOFA scores have good discrimination between survivors and nonsurvivors [32]. In addition, as in prior research [33][34][35][36], multiple organ dysfunction evidenced by high SOFA scores are associated with higher mortality. The use of proxy variables for SOFA scores has been validated in prior research.…”
Section: Discussionsupporting
confidence: 76%
“…[3,41] Prior clinical studies have suggested the majority of AKI in trauma develops late and generally as a complication of septic shock and/or progressive multiple organ dysfunction syndrome. [23][24][25]42] Alternatively, our study is strengthened by being the largest multi-center study of AKI in trauma performed to date. We contend our data provides a crude descriptive analysis of the occurrence of early AKI, defined by the RIFLE criteria, that is more likely to be attributable to trauma rather than to delayed or additional confounding factors (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The score can measure individual or aggregate organ dysfunction over time and is useful to evaluate morbidity. Although the SOFA scoring was not developed to predict outcome, the obvious relationship between organ dysfunction and mortality has been demonstrated in several studies [3,6,7].…”
Section: Problem Statementmentioning
confidence: 99%